Characterization of nanostructured pure aluminum tubes produced by tubular channel angular pressing (TCAP) - Mesbah, M.; Faraji, G.; Bushroa, Abdul Razak (Elsevier, 2014)
Ultrafine grained (UFG) aluminum tubes were fabricated by the tubular channel angular pressing (TCAP) process. The microstructural evolution was characterized by transmission electron microscopy (TEM) and mechanical properties were evaluated by compression test and hardness measurements. TEM analysis of specimen subjected to one TCAP pass showed the formation of an array of elongated subgrains with high angle grain boundaries. Increase in the number of passes changes the elongated grains to equiaxed grains with ~310 nm sizes. Microhardness value of the processed tubes was enhanced to 49.4 Hv after one pass from an initial value of 32.9 Hv. Yield and ultimate strengths were increased 2.5 and 2.28 times as compared to annealed specimen. Compression tests also showed that UFG aluminum tubes exhibit lower work hardening and almost perfect plastic behavior without any failure.